Has the HIV epidemic peaked? - Bongaarts, John (The Population Council, Inc. New YorkUS, 2008)
Reviews regional and country patterns of HIV epidemics and discusses possible causes of the geographic variation in epidemic sizes. Examines projections of the future course of the epidemic, estimates the peak years of regional epidemics, and briefly assesses the potential future impact of new prevention technologies.